Antimalarial dihydrochalcone isolated from Artocarpus sericicarpus Jarret leaves and in silico investigation against falcipain-2 protein - Lidya Tumewu; Hilkatul Ilmi; Ratih Dewi Saputri; Defi Kartika Sari; Adita Ayu Permanasari; Hanifah Khairun Nisa; Saipul Maulana; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung; Che Puteh Osman; Nor Hadiani Ismail; Aty Widyawaruyanti; et al. (Journal of Pharmacy & Pharmacognosy Research, 2023)
Aims: To investigate the potential antimalarial plant belonging to the Artocarpus genus, Artocarpus sericicarpus, and isolate the antimalarial active compound from leaves extract.